2021
DOI: 10.2147/pgpm.s320816
|View full text |Cite
|
Sign up to set email alerts
|

Economic Impact of the Application of a Precision Medicine Model (5SPM) on Psychotic Patients

Abstract: Background Schizophrenia is a severe mental disorder that often manifests within the first three decades of life. Its prognosis is uncertain and may result in a prolonged treatment that could extend throughout the entire lifespan of the patient. Antipsychotic drugs are characterized by a high interindividual variability when considering therapeutic effect and emergence of adverse effects. Such interindividual variability is thought to be associated primarily with pharmacokinetic matters. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 30 publications
1
10
0
Order By: Relevance
“…An economic impact of the model in psychotic patients has been previously reported [41]. In this study, we achieved a reduction in direct costs, including both hospitalization and pharmacotherapy, as well as a reduction in total costs in 67% of patients who underwent the application of this pharmacogenetic approach.…”
Section: Economic Implicationssupporting
confidence: 54%
“…An economic impact of the model in psychotic patients has been previously reported [41]. In this study, we achieved a reduction in direct costs, including both hospitalization and pharmacotherapy, as well as a reduction in total costs in 67% of patients who underwent the application of this pharmacogenetic approach.…”
Section: Economic Implicationssupporting
confidence: 54%
“…Indeed, outcome-oriented studies repeatedly demonstrate positive impacts of PGx on individuals [ 3 , 4 , 5 ], providers [ 6 , 7 ], and the healthcare system [ 8 , 9 ]. Oncology [ 10 , 11 ] and psychiatry [ 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 ] implementations demonstrate particularly well-documented improvements. Further, a variety of positive economic, clinical, and humanistic outcomes (ECHO) associated with PGx have also been described.…”
Section: Introductionmentioning
confidence: 99%
“…Carrascal-Laso et al 23 demonstrated that, before applying the pharmacogenetics test, participants in the study accounted for 504 hospitalization stays. This was reduced to 218 hospitalizations after adjusting treatment on the basis of the pharmacogenetics test.…”
Section: Resultsmentioning
confidence: 98%
“…Pharmacogenetics (treatment resistant) ( n = 42) versus TAU ( n = 62) Age, mean (years): 18.79 versus 13.83 Sex (% female): 26% versus 8% Ethnicity: N/A Medication (%): antipsychotics, 67 versus 32; antidepressants, 48 versus 11; anxiolytics, anticonvulsants and others, 26 versus 56; no current medication, 7 versus 0 Diagnosis: 100% autism spectrum disorder Symptom severity (using CGI and CGAS) Antipsychotics, antidepressants, anxiolytics and anticonvulsants CYP1A2 , CYP2C19 , CYP2D6 and SLC6A4 Studies with one comparator Carrascal-Laso et al 22 2020 Spain Retrospective observational study One arm: pharmacogenetics only Time horizon: 3 years Total sample ( n = 188) offered pharmacogenetics test. Age, median (years): 47 Sex (% female): 37.8% Ethnicity: N/A Medication (%): N/A Diagnosis (%): dementia, 0.53; substance-related disorder 6.38; schizophrenia, 67.02; persistent delusional disorder, 1.06; brief and acute psychotic disorder, 0.53; schizoaffective disorder, 6.92; bipolar disorder, 13.30; major depressive disorder, 0.53; specific personality disorder, 1.06; mixed personality disorder, 0.53; intellectual disability, 1.06 Mean daily dose Polytherapy cases Antipsychotics CYP1A2 , CYP2B6 , CYP2C9 , CYP2C19 , CYP2D6 , CYP3A5 and ABCB1 Carrascal-Laso et al 23 2021 Spain Retrospective observational study One arm: pharmacogenetics only Time horizon: 3 years Total sample ( n = 188) offered pharmacogenetics test. Age, median (years): 47 Sex (% female): 37.8% Ethnicity: N/A Medication (%): N/A Diagnosis (%): dementia, 0.53; substance-related disorder 6.38; schizophrenia, 67.02; persistent delusional disorder, 1.06; brief and acute psychotic disorder, 0.53; schizoaffective disorder, 6.92; bipolar disorder, 13.30; major depressive disorder, 0.53; specific personality disorder, 1.06; mixed personality disorder, 0.53; intellectual disability, 1.06 Pharmaceutical costs Hospitalization costs Antipsychotics CYP1A2 , CYP2B6 , CYP2C9 , CYP2C19 , CYP2D6 , CYP3A5 and ABCB1 Walden et al 25 2019 Canada Prospective observational study One arm: pharmacogenetics only Assessment points: baseline, 6 weeks and 12 weeks Total sample ( n ...…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation